Planonasus parini n. g. and n. sp., a new genus and species of false cat sharks (Carchariniformes, Pseudotriakidae) from the deep northwestern Indian Ocean off Socotra Islands - Weigmann, Simon; Stehmann, Matthias F.w.; Thiel, Ralf (Zootaxa, 2013)
A new genus and species of the carcharhiniform family Pseudotriakidae is described based on three specimens caught near the Socotra Islands in the northwestern Indian Ocean. The first specimen and holotype of Planonasus parini g. n. and sp. n. was caught during cruise 17 of RV ‘Vityaz’ in 1988/89 along the deep western Indian Ocean. Two further specimens of the new genus and species were caught somewhat later by commercial trawlers close to the locality of the holotype. The new genus differs from the two other pseudotriakid genera Gollum and Pseudotriakis by the presence of oral papillae, the absence of nicitating eyelids, a longer head, an intermediate prenarial snout length, an intermediate number of tooth rows per jaw, a first dorsal fin of intermediate height and length and with a white free rear tip, a caudal peduncle of inter-mediate length, and fewer vertebrae.